Od imitacji do kreacji. Sztuczna biżuteria w pierwszej połowie XX wieku - Lipczik, Agata (Załącznik Kulturoznawczy, 2019)
The article discusses the production of costume jewellery in the first half of the 20th century. During this period, the jewellery made of less expensive materials has undergone a revolution in terms of its function. In the 20th century, the adornments ceased to be only imitations of precious gems and gradually gained their own identity. Promoted by Coco Chanel and, later on, by other French fashion designers, costume jewellery has become an independent genre of body ornament. Due to its lower production costs,designers could experiment with various materials, giving free rein to artistic imagination. Costume jewellery was often designed by artists previously professionally associated with leading jewellery houses offering traditional jewellery. At the same time, the artists who later on worked in well-known jewellery companies, had been collecting their first experiences by designing costume jewellery. The two jewellery worlds constantly influenced each other, provoking themselves to develop. This trend was particularly noticeable in the USA where the production of costume jewellery has been a very important industry since the beginning of the 20th century.